New York Stories†: Narrating the Neighbourhood. Issue 3 (27th May 2017) - Irving, Andrew
ABSTRACT: New York Stories aims to research and represent the realms of inner expression that constitute people's lived experiences of urban space but remain beneath the surface of their public activity. The capacity for a complex inner lifeworld – consisting of inner speech, inchoate trajectories of thought, unarticulated moods, random urges, unsymbolised thinking, imagination, sensation, memory – is a distinctive feature of human experience that mediates many realms of everyday life, action and practice. By placing the problem of interiority directly into the field and turning it into an ethnographic, practice-based question to be addressed in collaboration with informants, New York Stories can be seen as an ethnographic attempt to research and represent the everyday experience of living with HIV/AIDS in New York's Lower East Side by examining the complex trajectories of thinking and being that are played out in public spaces but are not necessarily externalised.